Challenges for Next Generation Network Operations and Service Management 11th Asia-Pacific Network Operations and Management Symposium, APNOMS 2008, Beijing, China, October 22-24, 2008. Proceedings - Ma, Yan.; Choi, Deokjai; Ata, Shingo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 11th Asia-Pacific Network Operations and Management Symposium, APNOMS 2008, held in Beijing, China, in October 2008. The 43 revised full papers and 34 revised short papers presented were carefully reviewed and selected from 195 submissions. The papers are organized in topical sections on routing and topology management; fault management; community and virtual group management; autonomous and distributed control; sensor network management; traffic identification; QoS management; policy and service management; wireless and mobile network management; security management; short papers.
Session 1: Routing and Topology Management -- Session 2: Falut Management -- Session 3: Community and Virtual Group Management -- Session 4: Autonomous and Distributed Control -- Session 5: Sensor Network Management -- Session 6: Traffic Identification -- Session 7: QoS Management -- Session 8: Policy and Service Management -- Session 9: Wireless and Mobile Network Management -- Session 10: Security Management -- Session S1, S2: Short Papers.
Keywords: Computer science; Computer organization; Computer communication systems; Computer system failures; Computers; Electrical engineering; Computer Science; Computer Communication Networks; Communications Engineering, Networks; Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Electronic books